2016
DOI: 10.1139/cjz-2015-0094
|View full text |Cite
|
Sign up to set email alerts
|

Native prey distribution and migration mediates wolf (Canis lupus) predation on domestic livestock in the Greater Yellowstone Ecosystem

Abstract: Little research has evaluated how the migration and distribution of native prey influence patterns of livestock depredation by large carnivores. Previous research suggests that the presence of native prey can increase depredation rates by attracting predators (prey tracking hypothesis). Alternatively, the absence of native prey may facilitate predation on livestock (prey scarcity hypothesis). In this study, we evaluated support for these competing hypotheses through analysis of 4 years of cattle (Bos taurus L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…Wolves are opportunistic and prey switching can occur as a result of a number of factors (that are not mutually exclusive), including in response to seasonal and environmental changes (Nelson andMech 1986, Szepanski et al 1999), the occurrence of other predators (Kortello et al 2007, Merkle et al 2017, prey vulnerability (Bergman et al 2006, Garrott et al 2007, Metz et al 2012, or changes in the abundance of prey (Garrott et al 2007, Fortin et al 2015, Sand et al 2016. We found that winter diet for wolves centered on wild ungulates, particularly deer, which is what we had predicted.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Wolves are opportunistic and prey switching can occur as a result of a number of factors (that are not mutually exclusive), including in response to seasonal and environmental changes (Nelson andMech 1986, Szepanski et al 1999), the occurrence of other predators (Kortello et al 2007, Merkle et al 2017, prey vulnerability (Bergman et al 2006, Garrott et al 2007, Metz et al 2012, or changes in the abundance of prey (Garrott et al 2007, Fortin et al 2015, Sand et al 2016. We found that winter diet for wolves centered on wild ungulates, particularly deer, which is what we had predicted.…”
Section: Discussionsupporting
confidence: 69%
“…Gray wolves Canis lupus have been studied to examine both the direct and indirect effects of predation on other species, as well as conflicts with humans through predation on livestock (Wilmers et al 2003, Kortello et al 2007, Wit-tmer et al 2013, Nelson et al 2016, Santiago-Avila et al 2018. Wolf predation has been studied on wild ungulates such as deer (Odocoileus spp.…”
mentioning
confidence: 99%
“…These conservation strategies limited the lethal management of predators to a point where some species have recovered (Greater Yellowstone distinct population of grizzly bears delisted in 2017 8 due to recovery; gray wolves delisted nationally in 2013 with the exception of Wyoming which was delisted in 2017 9 ). Thus, while the historical human-predator paradigm has shifted from control to coexistence for some predators 10 , this paradigm shift has not occurred for all predators in all places and the complexity of livestock predation persists today 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the impacts of predation on livestock by carnivores is a well-documented conflict in conservation [15,51], the extent to which the occurrence of these impacts is mediated by wild herbivore prey remains unknown. Nelson et al [59] put forward two mechanisms to describe this interaction. The prey tracking hypothesis states that carnivores are attracted to their wild prey but kill livestock as a by-product where both types of herbivore co-occur [59].…”
Section: Livestock Production Within Complex Trophic Networkmentioning
confidence: 99%